PENGARUH NILAI INTRINSIK SAHAM DAN NILAI PASAR SAHAM DITINJAU DARI ANALISIS FUNDAMENTAL TERHADAP TINGKAT RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Putra, Dedi (Jurnal Manajemen dan Keuangan, 2010)
This research that is to prove the existence of difference among intrinsic value of stock market value and share at manufacturing business which enlist in Effect Exchange Indonesia. Method which is used in this research that is using quantitative analysis that is basal analysis which in the form of formula of price earning ratio which itâs converted into SPSS ver 12.0.The result in this research are : First hypothesis that is see assess t- test is 0,231 with probability of value is 0,819 two sides. the difference statistically, signifikan at level a equal to 0,05. at Second Hypothesis see that result of t â test equal to 2,847 with level of signifikan equal to 0,04. itâs meaning, that t â test > t tables of (2,847 > 2,05) and statistically signifikan at level Â£ equal to 0,05 or probability (sig) is 0,04 < 0,05. this matter have ameaning that there are influence among intrinsic value and share return. at third hypothesis that is showing reluts of t-test equal to 0,931 with level of signifikan equal to its 0,360 meaning. that t â test > t- tables of (2,931 > 2,05) and stastistically signifikan at level Â£ equal to 0,05 or probability (sig) is 0,032 < 0,05. this matter hav e a meaning of that there are infulance among market value and of return share.Keyword: market value, intrinsic value and return share.